PEMIKIRAN ABU ’UBAID - Devi Herawati; Dwi Marlena; Ananda Bintang; Fitri Hayati (JURNAL ILMIAH RESEARCH STUDENT, 2025)
Abu Ubaid al-Qasim ibn Sallam was an early Muslim scholar who made significant contributions to the development of Islamic economic thought, especially in the aspects of public finance and wealth distribution policies. His famous work, Kitab al-Amwal is one of the early writings that discusses economic concepts in Islam in detail, including zakat, kharaj, jizyah, and the management of the baitul mal. Abu Ubaid highlighted the importance of social justice and the responsibility of the state in ensuring an equitable distribution of wealth and meeting the needs of the poor. His views are rooted in the Qur'an and Sunnah, with an approach that emphasizes ethics, justice, and a balance between individual rights and the interests of society. The results of the study show that Abu Ubaid emphasized the importance of the principles of justice, transparency, and social responsibility in the management of state assets. This study explains Abu Ubaid's thoughts on Islamic economic theory and its relevance in the current economic context, especially regarding public policy and public finance.